Pelaksanaan Metode At-taisir dalam Menghafal Pada Kelas VII A Alquran di Pondok Pesantren - Gio Andrian; Indah Muliati (An-Nuha, 2023)
This study aims to find out how to plan, implement and evaluate the At-Taisir method in memorizing the Quran in class VII A students at the Taajul Huffazh Islamic Boarding School. The method that researchers use in this study is a qualitative method with a case study approach. The research instruments used are observation guidelines and interview guidelines. Researchers use data collection techniques, namely observation, interviews, documentation The source of the data was taken through informants, namely the Principal, Waka Kesiswaan and 5 students of class VII A as well as documents in the form of videos, photos, and other documents. Data analysis techniques use data reduction, data presentation, and conclusion drawing. The results of this study show the implementation of the At-Taisir method in memorizing the Quran in class VII A students at the Taajul Huffazh Islamic Boarding School Quran includes: Santri gather in the hall, take mushaf, read shalawat, pray, students are divided into groups, students are divided according to their ability level. The conclusion of the implementation of the At-taisir method at the Taajul Huffazh Islamic boarding school is carried out by after the students have memorized verses and then the students deposit their memorization to the supervisor teacher, after that they carry out muraja'ah activities every day, in pairs by testing rote memorization alternately both in terms of connecting verses , the position of the verse, the page of the verse, and the contents of the verse. This study aims to find out how to plan, implement and evaluate the At-Taisir method in memorizing the Quran in class VII A students at the Taajul Huffazh Islamic Boarding School. The method that researchers use in this study is a qualitative method with a case study approach. The research instruments used are observation guidelines and interview guidelines. Researchers use data collection techniques, namely observation, interviews, documentation The source of the data was taken through informants, namely the Principal, Waka Kesiswaan and 5 students of class VII A as well as documents in the form of videos, photos, and other documents. Data analysis techniques use data reduction, data presentation, and conclusion drawing. The results of this study show the implementation of the At-Taisir method in memorizing the Quran in class VII A students at the Taajul Huffazh Islamic Boarding School Quran includes: Santri gather in the hall, take mushaf, read shalawat, pray, students are divided into groups, students are divided according to their ability level. The conclusion of the implementation of the At-taisir method at the Taajul Huffazh Islamic boarding school is carried out by after the students have memorized verses and then the students deposit their memorization to the supervisor teacher, after that they carry out muraja'ah activities every day, in pairs by testing rote memorization alternately both in terms of connecting verses , the position of the verse, the page of the verse, and the contents of the verse.